2014
DOI: 10.1186/1753-6561-8-s1-s103
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis for genetic association studies: to do, or not to do? That is the question

Abstract: In Genetic Analysis Workshop 18 data, we used a 3-stage approach to explore the benefits of pathway analysis in improving a model to predict 2 diastolic blood pressure phenotypes as a function of genetic variation. At stage 1, gene-based tests of association in family data of approximately 800 individuals found over 600 genes associated at p<0.05 for each phenotype. At stage 2, networks and enriched pathways were estimated with Cytoscape for genes from stage 1, separately for the 2 phenotypes, then examining n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The three contributions that used simulated data [Almeida et al., ; Greco et al., ; Hu and Paterson, ] had the explicit knowledge of which genes were causal in the pathogenesis of hypertension; the other analyses relied on various proxy measures of causality. For example, both Dufresne et al [] and Edwards et al [] used only exonic variants, and all other analyses were restricted to variants that could be mapped to known genes. Aslibekyan et al [] explicitly compared variance contributions of SNVs within known blood pressure pathway genes with those of SNVs located within 50 kb upstream of the transcription start site and within 50 kb downstream of the stop codon; they found that genic regions played a more prominent role in the genetic architecture of hypertension than the flanking regions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The three contributions that used simulated data [Almeida et al., ; Greco et al., ; Hu and Paterson, ] had the explicit knowledge of which genes were causal in the pathogenesis of hypertension; the other analyses relied on various proxy measures of causality. For example, both Dufresne et al [] and Edwards et al [] used only exonic variants, and all other analyses were restricted to variants that could be mapped to known genes. Aslibekyan et al [] explicitly compared variance contributions of SNVs within known blood pressure pathway genes with those of SNVs located within 50 kb upstream of the transcription start site and within 50 kb downstream of the stop codon; they found that genic regions played a more prominent role in the genetic architecture of hypertension than the flanking regions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, despite a large number of options for pathway definitions, genome coverage was still low. For example, using Cytoscape [Shannon et al., ], Dufresne et al [] identified pathways for only 35% of the candidate genes (120 annotated genes of 600 in the selected list).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations